2017
DOI: 10.1111/odi.12631
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of aloe vera in management of oral lichen planus: a systematic review and meta‐analysis

Abstract: Although corticosteroids are still the gold standard, aloe vera shows promising results especially with no adverse effects compared with various adverse effects of corticosteroids. We recommend conducting new randomized clinical trials with larger sample size, sufficiently long follow-up period as well as standardized aloe vera formulations and outcome measures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
30
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 23 publications
2
30
0
5
Order By: Relevance
“…The pooled data of the three studies showed superiority of aloe vera in reducing pain in OSF patients especially at the end of the 1st and 2nd months, demonstrating good efficacy and quick action of aloe vera in reducing pain as compared to other treatment modalities. The outcome of this review corroborates previous systematic reviews which reported aloe vera to be effective in reducing mucosal pain in patients with various oral mucosal diseases including oral lichen planus, recurrent aphthous stomatitis, burning mouth syndrome, and radiation‐induced mucositis . Overall, the efficacy of aloe vera in alleviating signs and symptoms of OSF can be attributed to its analgesic and anti‐inflammatory properties .…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…The pooled data of the three studies showed superiority of aloe vera in reducing pain in OSF patients especially at the end of the 1st and 2nd months, demonstrating good efficacy and quick action of aloe vera in reducing pain as compared to other treatment modalities. The outcome of this review corroborates previous systematic reviews which reported aloe vera to be effective in reducing mucosal pain in patients with various oral mucosal diseases including oral lichen planus, recurrent aphthous stomatitis, burning mouth syndrome, and radiation‐induced mucositis . Overall, the efficacy of aloe vera in alleviating signs and symptoms of OSF can be attributed to its analgesic and anti‐inflammatory properties .…”
Section: Discussionsupporting
confidence: 85%
“…Recently, aloe vera has been introduced as a natural herbal alternative for the management of OSF . Aloe vera is an ancient plant that has several pharmacological benefits and has long been used as a remedy for numerous medical conditions without any reported side effects . Primarily, the medical benefits of aloe vera are attributed to its analgesic, anti‐inflammatory, immune‐modulatory, antioxidant, anti‐neoplastic, and wound‐healing properties .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[5] The main inconvenience of these treatments is represented by the side effects including insomnia, nervousness, fluid retention, electrolyte imbalance, hyperglycemia, osteoporosis, nephrotoxicity, gingival hyperplasia, nausea, and headache. [6] International Dental & Medical Journal of Advanced Research • Vol. 4 • 2018 Due to these side effects, the possibility of prolonged treatment with steroids, and the fact that the disease process could still last for years, an alternative therapy is desirable.…”
Section: Introductionmentioning
confidence: 99%
“…Topical treatment is a good choice because of its less harmful side effects. [6] Studies have demonstrated that AV has an important therapeutic uses in the management of oral lesions such as oral submucous fibrosis, radiation-induced mucositis, burning mouth syndrome, xerostomia, and recurrent aphthous ulcers. [8,9] The aim of the study is to evaluate the efficacy of AV gel in the treatment of OLP compared with placebo.…”
Section: Introductionmentioning
confidence: 99%